Labor economics - Pagoso, Cristobal M.; Dinio, Rosemary P. (Manila, 2006)
This book is written with the objective of providing students of economics and business with a basic understanding of labor issues, theories and problems as well as labor legislations relevant to these issues.
Keywords: Labor economics; Labor market- Philippines